Molecular Dynamics Simulation of Low-Cycle Fatigue Behavior of Single/Polycrystalline Iron - Tianyu Zhang; Jinjie Zhou; Jinchuan Shen (Nanomaterials)
The fatigue plastic mechanism and dislocation characteristics of engineering materials are the key to studying fatigue damage. In this study, the molecular dynamics (MD) method was employed to investigate the microstructural characteristics and fatigue mechanical properties of both single-crystalline and polycrystalline iron under varying strain amplitudes associated with cyclic hardening, cyclic softening, and cyclic saturation. The occurrence, accumulation, and formation process of the local plastic fatigue damage of monocrystalline/polycrystalline iron under fatigue load are discussed. The local plastic initiation and accumulation of single-crystal iron occur at the intersection of slip planes, which is the dislocation source. The 1/2<111> dislocation plays an important role in the fatigue plastic accumulation of single-crystal iron. Polycrystalline iron undergoes grain rotation and coalescence during cyclic loading. The grain size responsible for plastic deformation gradually increases. The initiation and accumulation of local plasticity occurs at the grain boundary, which eventually leads to fatigue damage at the grain boundary.